Antarctic ozone-hole investigation programme -Preliminary results of ozonesonde ascents during January-February 1987 (MAUSAM, 1988)
The paper summarises the preliminary resuits of ozonesonde ascents taken at GDR, Indian and Japanese stations in Antarctica during January-February 1987 ror intercomparison purpose. These ascents were taken as prelude to the international Antarctic ozone-hole investigation programme. The ozonesonde data or the Indian station, Dakshin Gangotri, is also compared with the observations taken at the station during the Second Indian Scientific Expedition to Antarctica (January-February 1983).